Mutational analysis of protein binding sites involved in formation of the bacteriophage lambda attL complex. - MacWilliams, M (1997)
Bacteriophage lambda site-specific recombination requires the formation of higher-order protein-DNA complexes to accomplish synapsis of the partner attachment (att) sites as well as for the regulation of the integration and excision reactions. The att sites are composed of a core region, the actual site of strand exchange, and flanking arm regions. The attL site consists of two core sites (C and C'), an integration host factor (IHF) binding site (H'), and three contiguous Int binding arm sites (P'1, P'2, and P'3). In this study, we employed bacteriophage P22 challenge phages to determine which protein binding sites participate in attL complex formation in vivo. The C', H', and P'1 sites were critical, because mutations in these sites severely disrupted formation of the attL complex. Mutations in the C and P'2 sites were less severe, and alteration of the P'3 site had no effect on complex formation. These results support a model in which IHF, bound to the H' site, bends the attL DNA so that the Int molecule bound to P'1 also interacts with the C' core site. This bridged complex, along with a second Int molecule bound to P'2, helps to stabilize the interaction of a third Int with the C core site. The results also indicate that nonspecific DNA binding is a significant component of the Int-core interactions and that the cooperativity of Int binding can overcome the effects of mutations in the individual arm sites and core sites.